Six new species of the spider genus Belisana Thorell, 1898 (Araneae: Pholcidae) from southern China - Zhu, Wenhui; Yao, Zhiyuan; Zheng, Guo; Li, Shuqiang (Zootaxa, 2020)
The genus Belisana Thorell, 1898 is diverse in southern China. In this study, six new species are described and illustrated: Belisana guilin sp. nov. (Guangxi; male, female), Belisana maoer sp. nov. (Sichuan; male, female), Belisana naling sp. nov. (Guangxi; male, female), Belisana xiyuan sp. nov. (Fujian; male, female), Belisana xuanguan sp. nov. (Guangxi; male) and Belisana yuexiu sp. nov. (Guangdong; male). In addition, Belisana is reported from Sichuan for the first time.